Kaji Eksperimental: Pengaruh Penambahan Outlet Duct Terhadap Nilai Thrust Pada Electric Ducted Fan - Farhan Fachrul Rozi (INOVTEK - SERI MESIN, 2021)
EDF (Electric Ducted Fan) is an electric-powered propulsion engine that is considered efficient in optimizing propulsion and aerodynamic forces on the fan. Beside the ducts addition in the fan area, the addition of ducts in other areas such as outlets can also affected the EDF performance. The 90mm EDF when normal conditions (factory settings) does not have a duct to direct the airflow out of the system. The implementation of this experimental study includes the manufacture of outlet duct geometry which is made in 3 variants of shapes (cylinder, covergent, convergent-divergent). Geometry is made using Solidwork software. Manufacturing activities are carried out using the 3D Printing method using  PLA (Polylactic Acid) type material. And testing activities are carried out under static testing conditions using a thrust meter. The result of this final project, there is a significant effect after the outlet duct addition on the EDF is given. The effect that occurs is a thrust value reduction by 6.65% to 48.64%.                                                                          Keyword: Experimental, EDF, Outlet Duct, Thrust